Possible role of intravenous administration of mesenchymal stem cells to alleviate interstitial cystitis/bladder pain syndrome in a Toll-like receptor-7 agonist-induced experimental animal model in rat - Hidetoshi Tabata (BMC, 2021)
Abstract Background Interstitial cystitis/bladder pain syndrome (IC/BPS) categorized with and without Hunner lesions is a condition that displays chronic pelvic pain related to the bladder with no efficacious treatment options. There are strong associations suggested between Hunner-type IC and autoimmune diseases. Recently, we established an animal model of Hunner-type IC using a Toll-like receptor-7 (TLR7) agonist. Intravenous infusion of mesenchymal stem cells (MSCs) can be used to treat injury via multimodal and orchestrated therapeutic mechanisms including anti-inflammatory effects. Here, we investigated whether infused MSCs elicit therapeutic efficacy associated with the TLR7-related anti-inflammatory pathway in our Hunner-type IC model. Methods Voiding behaviors were monitored 24 h prior to the Loxoribine (LX), which is a TLR7 agonist instillation in order to establish a Hunner-type IC model (from − 24 to 0 h) in female Sprague–Dawley rats. LX was instilled transurethrally into the bladder. At 0 h, the initial freezing behavior test confirmed that no freezing behavior was observed in any of the animals. The LX-instilled animals were randomized. Randomized LX-instilled rats were intravenously infused with MSCs or with vehicle through the right external jugular vein. Sampling tissue for green fluorescent protein (GFP)-positive MSCs were carried out at 48 h. Second voiding behavior tests were monitored from 72 to 96 h. After the final evaluation of the freezing behavior test at 96 h after LX instillation (72 h after MSC or vehicle infusion), histological evaluation with H&E staining and quantitative real-time polymerase chain reaction (RT-PCR) to analyze the mRNA expression levels of inflammatory cytokines were performed. Results Freezing behavior was reduced in the MSC group, and voiding behavior in the MSC group did not deteriorate. Hematoxylin–eosin staining showed that mucosal edema, leukocyte infiltration, and hemorrhage were suppressed in the MSC group. The relative expression of interferon-β mRNA in the bladder of the MSC group was inhibited. Numerous GFP-positive MSCs were distributed mainly in the submucosal and mucosal layers of the inflammatory bladder wall. Conclusion Intravenous infusion of MSCs may have therapeutic efficacy in a LX-instilled Hunner-type IC rat model via a TLR7-related anti-inflammatory pathway.